Molybdenum disulfide / tin disulfide heterojunction nano composite material as well as preparation method and application thereof

By constructing a heterojunction nanocomposite structure of molybdenum disulfide/tin disulfide, the photothermal and photocatalytic performance is improved, and the high power density and drug resistance of photothermal therapy in the treatment of bacterial infection wounds is solved, achieving efficient bacterial killing and biological treatment Compatibility, as an antibiotic alternative, has wide application potential.

CN119158599APending Publication Date: 2024-12-20WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410967531.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing photothermal therapy in bacterial infection wound treatment has high power density and long-term laser exposure damage to normal cells, bacterial cell wall thickness makes it difficult to completely kill bacteria at low temperatures, and heat-resistant bacteria produce drug resistance, reducing antibacterial ability The problem.

Method used

By constructing a heterojunction nanocomposite structure of molybdenum disulfide/tin disulfide, the light absorption capacity and photothermal conversion efficiency of the near-infrared region are significantly improved, and combined with photocatalytic properties, a synergistic photothermal antibacterial material is formed.

Benefits of technology

Under 808nm near-infrared light irradiation, the antibacterial time is shortened, the concentration of antibacterial materials is reduced, and the good biocompatibility and antibacterial properties are achieved. It is used as an antibiotic alternative to treat bacterial infection wounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158599A_ABST
    Figure CN119158599A_ABST
Patent Text Reader

Abstract

The invention discloses a molybdenum disulfide / tin disulfide heterojunction nano composite material, which is constructed through hydrothermal reaction by taking transition metal sulfide as a matrix on the basis of photothermal and photocatalytic antibacterial principles. The light absorption capacity in a near-infrared region is remarkably improved, the composite material has good photo-thermal conversion efficiency and photocatalytic performance, the composite material generates a synergistic efficient sterilization effect, the problems that a single photo-thermal agent is long in illumination time, insufficient in antibacterial efficiency and the like are solved, and the composite material further has good biocompatibility and can be used for preparing the antibacterial material. The method has great application potential in the field of medical sterilization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of medical materials and relates to a molybdenum disulfide / tin disulfide heterojunction nanocomposite material. The invention also relates to a preparation method of the composite material and application of the composite material in light sterilization. Background Art

[0002] Currently, bacterial infection and bacterial resistance have become the main challenges in wound treatment and management. Therefore, there is an urgent need to develop safe and effective new antibacterial materials for the treatment of bacterially infected wounds. Since Pasteur proposed the pasteurization method in 1862, heat treatment has been shown to have a certain effect on the removal of all pathogens. In recent years, photothermal therapy (PTT) based on near-infrared light excitation has gradually been used in the treatment of infected wounds. Because it does not produce drug resistance and has a broad spectrum of antibacterial properties, it has become the most promising alternative to antibiotics.

[0003] Recent studies have found that molybdenum disulfide (MoS2), which is abundant and low in cost, has excellent photocatalytic properties. The Mo layer of molybdenum disulfide is located between two S layers, and the van der Waals force between adjacent layers is weak, which makes it easy to construct two-dimensional single-layer or multi-layer MoS2 nanosheets, thereby providing a high surface area and an adjustable band edge potential between 1.2-1.9 eV, making it promising for photocatalytic and photothermal applications. As a typical metal chalcogenide semiconductor, tin disulfide has a hexagonal CdI2-type crystal structure, is easy to prepare, has high photoelectric activity, excellent carrier mobility, stable composition and good biocompatibility. These characteristics make SnS2 widely used in fields such as lithium-ion batteries, gas sensors and photocatalysis. However, SnS2 has weak light absorption in the near-infrared region, which limits its application in near-infrared light-responsive semiconductor photothermal therapy.

[0004] Photothermal therapy based on various near-infrared light (NIR)-triggered nanoagents has become a rising star in the medical field due to its high spatial resolution, low side effects, minimal invasiveness, and deep tissue penetration. However, there are still certain disadvantages in relying solely on MoS2 photothermal treatment for sterilization. First, the surrounding normal cells / tissues may be damaged by high power density and long-term exposure to laser. Second, due to the thick cell wall of bacteria, it is still difficult to completely kill bacteria in a short time at low temperatures. Finally, some drug-resistant bacteria will develop heat resistance during high temperature processes, thereby reducing the antibacterial ability of nanomaterials. Therefore, MoS2 needs to cooperate with other effective strategies to make up for the shortcomings of single photothermal therapy, thereby shortening the antibacterial time, reducing the antibacterial power, and reducing the concentration of antibacterial materials.

[0005] Based on this, the present invention forms a heterojunction nanostructure by compounding molybdenum disulfide and tin disulfide. This composite structure can significantly improve the light absorption capacity in the near-infrared region, maximize the localized surface plasma effect of the near-infrared window, and thus significantly improve the photothermal performance of a single photothermal agent, thereby serving as an alternative to antibiotics to treat bacterially infected wounds. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a molybdenum disulfide / tin disulfide heterojunction nanocomposite material and its preparation method and application. The present invention is based on the principle of photothermal and photodynamic antibacterial, takes transition metal sulfide as the matrix, and constructs a molybdenum disulfide / tin disulfide heterojunction nanocomposite structure through a hydrothermal reaction, which significantly improves its light absorption capacity in the near-infrared region. The prepared composite photothermal agent has good photothermal conversion efficiency and photocatalytic performance, and can synergistically kill bacteria under near-infrared light irradiation, which well solves the problems of long illumination time and low antibacterial efficiency of a single photothermal agent, and has great application potential in the preparation of infected wound repair materials.

[0007] The purpose of the present invention is achieved through the following technical solutions: A molybdenum disulfide / tin disulfide heterojunction nanocomposite material comprises a molybdenum disulfide / tin disulfide heterojunction nanostructure, which is composed of flower-shaped molybdenum disulfide and hexagonal lamellar tin disulfide fixed on the molybdenum disulfide, wherein the diameter of the molybdenum disulfide is 300nm-500nm, and the diameter of the tin disulfide is 200nm-400nm.

[0008] The present invention further provides a method for preparing the molybdenum disulfide / tin disulfide heterojunction nanocomposite material, comprising the following steps: Sodium molybdate and tin tetrachloride are dissolved in water, then excess thiourea is added, and the pH is adjusted with anhydrous citric acid. The mixed solution is then heated to 180-250°C for hydrothermal reaction to obtain a suspension containing a composite material. Finally, the molybdenum disulfide / tin disulfide heterojunction nanocomposite material is obtained after centrifugation, washing, drying and grinding.

[0009] Preferably, the molar ratio of sodium molybdate to tin tetrachloride is 3-6:1.

[0010] Preferably, the pH is 1-4.

[0011] Preferably, the temperature of the hydrothermal reaction is 220° C. and the time is 24 h.

[0012] The molybdenum disulfide / tin disulfide heterojunction nanocomposite material provided by the present invention can be used for photothermal sterilization for non-therapeutic purposes, or for preparing photothermal sterilizers. The material absorbs near-infrared light and converts it into heat, while catalyzing the generation of active oxygen, thereby achieving efficient killing of bacteria.

[0013] The present invention further provides a non-therapeutic in vitro sterilization method, comprising the following steps: adding the molybdenum disulfide / tin disulfide heterojunction nanocomposite material to a bacterial solution containing bacteria, and then irradiating the solution with near-infrared light.

[0014] The principles or mechanisms involved in the present invention are: To solve the problems mentioned in the background technology, we tried to compound SnS2 and MoS2 to form a heterojunction nanostructure. This composite structure can significantly improve its light absorption capacity in the near-infrared region, maximize the localized surface plasma effect in the near-infrared window, and synergize the photocatalytic effect to produce a large amount of ROS under near-infrared light irradiation, thereby significantly improving the antibacterial properties of the composite material.

[0015] The possible mechanism of the synergistic effect of the combination of the two is as follows: Both SnS2 and MoS2 have certain light absorption properties, which can form photoexcited and plasma-induced electron-hole pairs on the surface. Especially for SnS2, the bottom energy of its conduction band (CB) is about 0.58 eV, which is higher than the top of the valence band (VB) of MoS2, which allows the holes generated in the valence band of MoS2 to quickly recombine with the electrons generated in the conduction band of SnS2. Because of this effective recombination of electron-hole pairs, the electrons in the conduction band of MoS2 and the holes in the valence band of SnS2 are concentrated together. Subsequently, these aggregated electrons combine with oxygen (O2) to form singlet oxygen ( 1 O2), while holes are directly converted into hydroxyl radicals ( .OH). Therefore, a direct heterojunction system is formed between SnS2 and MoS2, which greatly improves the photocatalytic performance. In this composite system, reactive oxygen species (ROS) act as strong oxidants, which damage cell membranes and cell walls by destroying important biomacromolecules such as DNA, RNA, and proteins of pathogens, and oxidize proteins and lipids in cells, ultimately leading to the death of pathogens. In addition, a large amount of heat is released during the photocatalytic process. The SnS2@MoS2 composite can generate more heat, which is mainly attributed to the following three factors: First, SnS2@MoS2 particles show higher photothermal conversion efficiency due to their localized surface plasmon resonance (LSPR) effect. Second, according to the equation ε=Aπ / 6d3FNALCwt, an increase in absorbance ("A") will lead to an increase in the extinction coefficient (ε). After SnS2@MoS2 composite, it has high absorbance in the ultraviolet to near-infrared band, indicating that it can absorb more light energy and release more heat. Third, MoS2 microspheres are assembled with SnS2 nanosheets to form a SnS2@MoS2 composite structure. Under light, the nanosheets can absorb some photons, while the remaining photons will be reflected between the nanosheets until most of the photons are absorbed. The multiple reflections and absorption of photons significantly increase the oscillation frequency of holes, further enhancing the photothermal conversion efficiency. In addition, when the size of the particles or cavities is close to the wavelength of light, light absorption is also significantly enhanced. The modified SnS2@MoS2 material is closer in size to the wavelength of the light source, which further improves the light absorption and photothermal conversion performance.

[0016] Compared with the prior art, the beneficial effects of the present invention include: (1) The present invention uses molybdenum disulfide as the base material, modifies it with tin disulfide, and adopts a hydrothermal method to construct a heterojunction nanostructure, which effectively improves its light absorption capacity in the near-infrared region and maximizes the localized surface plasma effect of the near-infrared window, thereby significantly improving the photothermal conversion and catalytic efficiency.

[0017] (2) The photothermal antibacterial material prepared by the present invention can achieve a sterilization rate of 99.9% within 15 minutes under 808nm near-infrared light irradiation, thereby reducing the chance of chronic wound infection. At the same time, the Mo and S elements in the composite material are essential trace elements for humans and have good biocompatibility and antibacterial properties. It is expected to be used as an alternative to antibiotics to treat bacterially infected wounds.

[0018] (3) The raw materials used in the present invention are widely available, low in price, and have a simple preparation process. Thiourea is used as the sulfur source, and a heterojunction nanostructure is constructed through a one-step hydrothermal reaction, which is simple and rapid to obtain a composite photothermal agent of uniform size.

[0019] (4) The solvent in the preparation process of the present invention has a wide range of sources and is easy to obtain. No waste gas is generated during the entire process, and the reaction waste liquid is easy to collect and treat. The present invention prepares a photothermal antibacterial material with excellent performance, which promotes the development of the medical sterilization field. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The following are scanning electron microscope (SEM) images of the products prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0021] Figure 2 The X-ray powder diffraction (XRD) patterns of Example 1, Comparative Example 1 and Comparative Example 2 are shown in FIG.

[0022] Figure 3 It is a comparison chart of the light and heat performance tests of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2.

[0023] Figure 4 The figure is a comparison chart of the active oxygen detection experimental results of Example 1, Comparative Example 1 and Comparative Example 2.

[0024] Figure 5 The following is a comparison chart of the effects of the products of Example 1, Comparative Example 1 and Comparative Example 2 in the antibacterial experiment. (In Figure a, the detection bacteria is Escherichia coli; in Figure b, the detection bacteria is Staphylococcus aureus) Figure 6 The cytotoxicity test results of the product of Example 1 at different concentrations are shown in FIG. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0026] Example 1 The preparation method of the molybdenum disulfide / tin disulfide composite material comprises the following steps: 0.68175 g (2.8 mmol) of sodium molybdate dihydrate, 0.2145 g (0.6 mmol) of tin tetrachloride pentahydrate and excess thiourea (0.978 g, 12.8 mmol) were weighed and added into 60 ml of ultrapure water, stirred and dissolved for 30 min, citric acid was added to adjust the pH to 3.0, and then ultrasonically treated for 30 min. The prepared mixed solution was then placed in a hydrothermal reactor and reacted at 220 ° C for 24 h to obtain a composite material suspension. The suspension was centrifuged at 8000 r / min for 10 min to remove the supernatant. The precipitate was washed with ultrapure water and anhydrous ethanol for 3 times in sequence and centrifuged. Finally, it was vacuum dried for 10 h. The dried block solid was ground with an agate mortar for 30 min to obtain a molybdenum disulfide / tin disulfide composite material.

[0027] Chemical reactions occurring during the preparation process: The reaction process involved in the synthesis of tin disulfide: First, tin tetrachloride pentahydrate dissociates into tin ions and chloride ions in the solution, and the reaction formula is: SnCl4·5H2O→Sn 4+ +4Cl − +5H2O (1) Then, citric acid and tin ions undergo complexation to form a stable tin-citric acid complex, and the reaction formula is: Sn 4+ +C6H8O7 → [C6O7H5] 3- Sn 4+ +3H + (2) Secondly, thiourea reacts with water under high temperature and pressure to generate ammonia (NH3) and hydrogen sulfide (H2S). The reaction formula is: SC(NH2)2+2H2O→CO2+2NH3+H2S (3) Finally, the generated hydrogen sulfide reacts with the tin-citric acid complex to generate tin disulfide precipitation, and the reaction formula is: [C6O7H5] 3- Sn 4+ +2H2S→SnS2+ C6H8O7+H + (4) The overall reaction equation is: SnCl4·5H2O +2SC(NH2)2→SnS2+2CO2+4NH4Cl+H2O (5) (Citric acid plays a complexing role in the reaction, stabilizing the tin ions and preventing them from directly reacting with hydrogen sulfide to form other forms of tin compounds.) The reaction process involved in the synthesis of molybdenum disulfide: First, thiourea reacts with water under high temperature and pressure to decompose into hydrogen sulfide (H2S). The reaction formula is: SC(NH2)2+2H2O→CO2+2NH3+H2S (1) Then, H2S acts as a sulfur source and reducing agent to convert MoO4 2- The Mo(VI) in the reaction is reduced to Mo(IV) and generates MoS2. The reaction formula is: 3Na2MoO4·2H2O+10H2S→ SO2+3MoS2 +3Na2S+16H2O (2) The overall reaction equation is: 3Na2MoO4·2H2O +10SC(NH2)2+4H2O→3MoS2+3Na2S+SO2+10CO2+20NH3 (3) Example 2 Except that the mass ratio of sodium molybdate dihydrate to tin tetrachloride pentahydrate in step S1 is 1:1.888, that is, sodium molybdate dihydrate is 0.227 g (0.9 mmol) and tin tetrachloride pentahydrate is 0.429 g (1.2 mmol), the other steps are the same as those in Example 1.

[0028] Example 3 Except that the mass ratio of sodium molybdate dihydrate to tin tetrachloride pentahydrate in step S1 is 8.495:1, that is, sodium molybdate dihydrate is 0.909 g (3.8 mmol) and tin tetrachloride pentahydrate is 0.107 g (0.3 mmol), the other steps are the same as those in Example 1.

[0029] Comparative Example 1 Weigh 0.968g (4mmol) sodium molybdate dihydrate and 1.220g thiourea (16mmol) and add them to 60ml ultrapure water, stir and dissolve for 30min, place the mixed solution in a hydrothermal reactor and react at 220℃ for 24h to obtain a molybdenum disulfide suspension; centrifuge the suspension at 8000r / min for 10min to remove the supernatant, wash the precipitate with ultrapure water and anhydrous ethanol three times in sequence and centrifuge. Finally, vacuum dry for 10h, grind the dried block solid with an agate mortar for 30min to obtain a molybdenum disulfide powder material.

[0030] Comparative Example 2 Weigh 0.524g (1.5mmol) of tin tetrachloride pentahydrate and 0.864g (11.35mmol) of thiourea and add them to 60ml, stir and dissolve for 30min, add 1.44g (7.5mmol) of anhydrous citric acid to adjust the pH, and ultrasonically treat for 30min; place the mixed solution in a hydrothermal reactor and react at 180℃ for 12h. After the suspension is cooled, centrifuge at 8000r / min for 10min to remove the supernatant, wash the precipitate with ultrapure water and anhydrous ethanol three times in sequence and centrifuge. Finally, vacuum dry for 10h, grind the dried block solid with an agate mortar for 30min to obtain tin sulfide powder material.

[0031] The embodiments and comparative examples were characterized and tested 1. Microscopic morphology observation The product of Example 1 was observed using a scanning electron microscope (SEM) S-4800 microscope at an accelerating voltage of 5 kV.

[0032] Figure 1From the microscopic morphology of the product prepared in Example 1 of the present invention, it can be seen that: MoS2 has a flower-ball-like structure with a diameter of 300nm-500nm, SnS2 has a flat hexagonal structure with a diameter of 200nm-400nm, and after the two are compounded by hydrothermal reaction, nearly hexagonal flaky substances are attached to the surface of the flower-ball-like MoS2, indicating that the molybdenum disulfide / tin sulfide heterojunction nanostructure is successfully constructed.

[0033] 2. XRD spectrum Figure 2 The XRD spectra of Example 1, Comparative Example 1 and Comparative Example 2 prepared by the present invention show the corresponding characteristic peaks from the three curves in the figure. 14.1, 33.3, 39.5 and 58.9 correspond to the (0 0 2), (1 00), (1 0 3) and (0 0 6) planes of hexagonal 2H-MoS2, respectively; the characteristic peaks of the two components of the comparative example at 2θ are 14.9°, 28.2°, 32.1°, 41.8°, 49.9°, 52.4° and 54.9°, respectively, corresponding to the (001), (100), (101), (102), (110), (111) and (103) 2T-SnS2 crystal planes. The characteristic peaks of Comparative Example 1 and Comparative Example 2 exist in the synthesized composite photothermal agent at the same time, and there are fewer impurity peaks in the XRD spectrum, indicating that the composite photothermal agent is successfully prepared.

[0034] 3. Photothermal performance test First, the dispersions of Comparative Example 1, Comparative Example 2 and Example 1, Example 2 and Example 3 with a concentration of 0.5 mg / ml were prepared, and the power density was 0.5 W / cm 2 , 1 ml of Mili-Q, Comparative Example 1, Comparative Example 2, and Example 1, Example 2, and Example 3 solution were irradiated with a near infrared laser (NIR) with a wavelength of 808 nm for 15 minutes each, and the temperature was recorded every 3 minutes using a temperature probe. Three parallel samples were set for each group for testing and data were recorded. Figure 3 It is a photothermal performance curve diagram of pure water, comparative example 1, comparative example 2 and embodiment 1, embodiment 2, embodiment 3. Figure 3 It can be seen that Comparative Examples 1 and 2 have certain photothermal properties, while the photothermal properties of the modified Examples 1, 2 and 3 are all improved, and the photothermal conversion efficiency of Example 1 is most significantly improved. Under the irradiation of near-infrared laser (NIR) with a wavelength of 808 nm, the temperature can be raised to 54.6°C within 15 minutes, and it has a higher photothermal antibacterial potential.

[0035] 4. Reactive oxygen detection Singlet oxygen ( 1 O2) and superoxide anion (˙O2 -) is the key factor affecting the photocatalytic activity. In order to study the photocatalytic performance of the composite material, 1,3-diphenylbenzofuran (DPBF) and nitrotetrazolyl blue chloride (NBT) were used for detection.

[0036] Singlet oxygen ( 1 O2) Detection: Under light-proof conditions, DPBF was dissolved in anhydrous ethanol, and the powders of Example 1, Comparative Example 1 and Comparative Example 2 were dissolved in the above 1,3-diphenylbenzofuran (DPBF) solution, and irradiated under 808nm near-infrared light for 1 min, respectively, and the supernatant was collected, and the ultraviolet spectrum of the solution was measured by an ultraviolet spectrophotometer.

[0037] Superoxide anion (˙O2 - ) Detection: Under light-proof conditions, nitro blue tetrazolyl chloride (NBT) was dissolved in anhydrous ethanol, and the powders of Example 1, Comparative Example 1 and Comparative Example 2 were dissolved in the above NBT solution, and the mixture was irradiated under 808 nm near-infrared light for 1 min, the supernatant was collected, and the ultraviolet spectrum of the solution was measured by an ultraviolet spectrophotometer.

[0038] The fluorescence signal of DPBF can be 1 O2 quenching,˙O2 - It can reduce NBT to formazan, which eventually leads to a decrease in the absorbance of the above two detection reagents at their respective maximum absorption wavelengths. Figure 4 It can be seen that both comparative examples 1 and 2 can reduce the absorbance of the detection reagent, and the material after the hydrothermal compounding can produce more singlet oxygen ( 1 O2) and superoxide anion (˙O2 - ), significantly improving the photocatalytic activity and generating more active oxygen.

[0039] 5. Antibacterial test The antibacterial properties of the materials were characterized by the plate counting method under 808nm near-infrared light irradiation.

[0040] Detection bacteria: Staphylococcus aureus ATCC6538, Escherichia coli ATCC25922.

[0041] Using PBS buffer solution as solvent, the powder materials of Example 1, Comparative Example 1 and Comparative Example 2 were diluted with PBS solution and added into bacterial solutions of Escherichia coli and Staphylococcus aureus respectively (the final concentration of the sample was 0.5 mg / ml and the final concentration of the bacterial solution was 1×10 7CFU / ml). Then, the mixture was transferred to a 48-well plate and irradiated under 808nm near-infrared light for 15min. 100ul of the irradiated mixture was diluted 500 times with PBS, and 100ul of the dilution was finally spread on an LB agar plate and inverted for 12h in the dark. The antibacterial activity of the sample was detected by visually observing the number of colonies.

[0042] Figure 5 a is a photo comparing the effects of the powder materials of Example 1, Comparative Example 1 and Comparative Example 2 in an antibacterial experiment (the bacteria used for detection is Escherichia coli); Figure 5 It can be seen from a that some colonies still exist after coating the plates in Comparative Examples 1 and 2, while there are basically no surviving colonies after coating the plates in Example 1, indicating that the modified composite material has excellent antibacterial properties.

[0043] Figure 5 b is a photo comparing the effects of the powder materials of Example 1, Comparative Example 1 and Comparative Example 2 in an antibacterial experiment (the bacteria used for detection is Staphylococcus aureus); Figure 5 b It can be seen that: some colonies still exist after the comparative examples 1 and 2 are coated, while there are basically no surviving colonies after the embodiment 1 is coated, indicating that the modified composite material has excellent antibacterial properties.

[0044] 6. In vitro cytotoxicity test: The powder composite material of Example 1 was sterilized and then immersed in complete culture medium (10% FBS (fetal bovine serum) + 1% PS (penicillin-streptomycin) + 89% DMEM) at concentrations of 0.5 mg / mL, 1 mg / ml and 3 mg / ml for 24 hours, and then fibroblasts (NIH3T3 cells) were seeded in a 96-well plate at a seeding density of 5000 cells / well. The plate was placed in a 37°C incubator for 24 hours, and then the culture medium was aspirated, and the culture medium soaked with the composite material was transferred to the 96-well plate, and continued to be cultured in the incubator. After 24 hours, the culture medium was discarded, and the cells were washed twice with PBS buffer. A mixture containing MTT (thiazolyl blue) and complete culture medium was added to each well in the dark. The mixing ratio of MTT and culture medium was 1:9. After incubation at 37°C for 4 hours, the supernatant was carefully aspirated. 200 μL of dimethyl sulfoxide (DMSO) was added to each well to dissolve the blue-purple crystals at the bottom of the plate, and the absorbance was detected at 490 nm using an enzyme reader. The complete culture medium was the negative control group, and the mixture containing 10% phenol and complete culture medium was the positive control group.

[0045] Figure 6 This is a comparison chart of the cytotoxicity test results of the composite material of Example 1 of the present invention at different concentrations; Figure 5It can be seen that the cell viability of the composite materials with concentrations of 0.5 mg / mL, 1 mg / ml and 3 mg / ml are 97.54%, 97.20% and 94.57% respectively, and the material toxicity level is level 1.

[0046] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A molybdenum disulfide / tin disulfide heterojunction nanocomposite material, characterized in that: include: The molybdenum disulfide / tin disulfide heterojunction nanostructure is composed of flower-ball-shaped molybdenum disulfide and hexagonal lamellar tin disulfide fixed on the molybdenum disulfide, wherein the diameter of the molybdenum disulfide is 300nm-500nm, and the diameter of the tin disulfide is 200nm-400nm.

2. The method for preparing the molybdenum disulfide / tin disulfide heterojunction nanocomposite material according to claim 1, characterized in that: The steps include: Sodium molybdate and tin tetrachloride are dissolved in water, then excess thiourea is added, and the pH is adjusted with anhydrous citric acid. The mixed solution is then heated to 180-250°C for hydrothermal reaction to obtain a suspension containing a composite material. Finally, the molybdenum disulfide / tin disulfide heterojunction nanocomposite material is obtained after centrifugation, washing, drying and grinding.

3. The preparation method according to claim 2, characterized in that: The molar ratio of sodium molybdate to tin tetrachloride is 3-6:

1.

4. The preparation method according to claim 2, characterized in that: The pH is 1-4.

5. The preparation method according to claim 2, characterized in that: The temperature of the hydrothermal reaction is 220° C. and the time is 24 h.

6. Use of the molybdenum disulfide / tin disulfide heterojunction nanocomposite material according to claim 1 in the preparation of a photothermal sterilizer.

7. The use according to claim 6, characterized in that: The composite material absorbs near-infrared light and converts it into heat, while catalyzing the generation of active oxygen, thereby achieving efficient killing of bacteria.

8. A non-therapeutic in vitro sterilization method, characterized in that The following steps are involved: The molybdenum disulfide / tin disulfide heterojunction nanocomposite material according to claim 1 is added to a bacterial solution containing bacteria, and then irradiated with near-infrared light.